Anisotropy of cell division and epithelial sheet bending via apical constriction shape the complex folding pattern of beetle horn primordia. (August 2018) - Adachi, Haruhiko; Matsuda, Keisuke; Niimi, Teruyuki; Inoue, Yasuhiro; Kondo, Shigeru; Gotoh, Hiroki
Abstract: Insects can dramatically change their outer morphology at molting. To prepare for this drastic transformation, insects generate new external organs as folded primordia under the old cuticle. At molting, these folded primordia are physically extended to form their final outer shape in a very short time. Beetle horns are a typical example. Horn primordia are derived from a flat head epithelial sheet, on which deep furrows are densely added to construct the complex folded structure. Because the 3D structure of the pupa horn is coded in the complex furrow pattern, it is indispensable to know how and where the furrows are set. Here, we studied the mechanism of furrow formation using dachsous ( ds ) gene knocked down beetles that have shorter and fatter adult horns. The global shape of the beetle horn primordia is mushroom like, with dense local furrows across its surface. Knockdown of ds by RNAi changed the global shape of the primordia, causing the stalk region become apparently thicker. The direction of cell division is biased in wildtype horns to make the stalk shape thin and tall. However, in ds knocked down beetles, it became random, resulting in the short and thick stalk shape. On the other hand, a fine and dense local furrow was not significantly affected by the ds knockdown. In developing wildtype horn primordia, we observed that, before the local furrow is formed, the apical constriction signal emerged at the position of the future furrow, suggesting the pre-pattern for the fine furrow pattern. According to the results, we propose that development of complex horn primordia can be roughly divided to two distinct processes, 1) development of global primordia shape by anisotropic cell division, and 2) local furrow formation via actin-myosin dependent apical constriction of specific cells. Highlights: Beetle horn is formed as the complex folded primordia with furrows. Developmental basis for making specific shape and furrow of primordia was investigated. Knockdown of gene dachsous can change the shape of primordia. Anisotropic cell division affects the global shape of the horn primordia. Apical constriction of specific cells likely to form the local furrows on the primordia